HEPATITIS B VIRUS SEROPREVALENCE AND IMPACT ON FERTILITY IN COUPLES AT THE GYNAECOLOGICAL ENDOSCOPIC SURGERY AND HUMAN REPRODUCTIVE TEACHING HOSPITAL, CAMEROON - Voundi, Joseph Emmanuel Voundi; Ndoua, Claude Noa; Voundi, Esther Voundi; Belinga, Etienne; Nyada, Serge; Ngono, Vanina; Mviena, Louise Nyimbe; Ayangma, Celestin Roger; Nogue, Raissa Kamga; Tsague, Nguefack; Toukam, Michel (Journal of Advanced Research in Medical and Health Science (ISSN 2208-2425), 2022)
Introduction: Hepatitis B virus (HBV) has been shown to have adverse effects on fertility in both women and men. Objective: to determine the seroprevalence of the hepatitis B virus and its impact on fertility in couples followed for infertility at the Gynaecological Endoscopic Surgery and Human Reproductive Teaching Hospital, Cameroon. Patients and methods: an analytical cross-sectional study was conducted over a period from January 1 to September 1, 2019, i.e., a period of 9 months at GESHRTH. Complete records were included in our study consecutively. Qualitative variables were compared using a Chi² test or Fisher’s exact test using Epi Info software version 3.5.4. The statistical significance threshold was set at 5%. Results and discussion: of the 279 couples selected, 54/558 (9.7%) people were positive for HBsAg including 33 (11.8%) women and 21 (7.5%). HBsAg-negative women were 5.55 times more likely to have uterine myomas (p = 0.006) and HBV-infected men were 7 times more likely to develop a sperm abnormality (p = 0.002) and 4 times more likely to have oligospermia (p = 0.005). Conclusion: the prevalence of HBV infection in couples followed for infertility remains high. HBV could have an impact on the occurrence of uterine myomas and sperm abnormalities.